2017
DOI: 10.1021/acscatal.7b01194
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Relations and Kinetic Monte Carlo Simulations To Bridge the Materials Gap in Heterogeneous Catalysis

Abstract: Scaling relations combined with kinetic Monte Carlo simulations are used to study catalytic reactions on extended metal surfaces and nanoparticles. The reaction energies are obtained by density functional theory calculations, where the site-specific values are derived using generalized coordination numbers. This approach provides a way to handle the materials gap in heterogeneous catalysis. CO oxidation on platinum is investigated as an archetypical reaction. The kinetic simulations reveal clear differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 58 publications
2
107
1
Order By: Relevance
“…Ther eaction is strongly influenced by complex kinetic couplings between sites,a nd am ultitude of sites leads to ahigh TOF. Thus,taking the site-assembly into account is key in understanding catalytic reactions over nanoparticles.CO oxidation over Pt is modeled using the following reaction Scheme:TheM onte Carlo simulations are carried out using the recently introduced scaling relation Monte Carlo (SRMC) method [21] (See also the Supporting Information). In SRMC, the adsorption energies and energy barriers on each site are treated using scaling relations in the generalized coordination numbers [14,15] (CN).…”
mentioning
confidence: 99%
“…Ther eaction is strongly influenced by complex kinetic couplings between sites,a nd am ultitude of sites leads to ahigh TOF. Thus,taking the site-assembly into account is key in understanding catalytic reactions over nanoparticles.CO oxidation over Pt is modeled using the following reaction Scheme:TheM onte Carlo simulations are carried out using the recently introduced scaling relation Monte Carlo (SRMC) method [21] (See also the Supporting Information). In SRMC, the adsorption energies and energy barriers on each site are treated using scaling relations in the generalized coordination numbers [14,15] (CN).…”
mentioning
confidence: 99%
“…[17,21] We note that CO oxidation is an exothermic reaction. In addition to the size dependence,the reaction conditions influence the most active geometry,a sthea ctive site changes with reaction conditions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[4][5][6][7] Theoretically, density functional theory [8,9] (DFT) calculations have outlined how adsorption properties depend on particle geometry, [10,11] which has been rationalized by descriptors such as coordination numbers and d-band centers. Thus,taking the site-assembly into account is key in understanding catalytic reactions over nanoparticles.CO oxidation over Pt is modeled using the following reaction Scheme:TheM onte Carlo simulations are carried out using the recently introduced scaling relation Monte Carlo (SRMC) method [21] (See also the Supporting Information). [13,16] However,t reating sites as isolated entities implies that kinetic couplings between the sites are neglected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the atop GCN has been adopted to estimate current densities and mass activities of electro-catalysts, for oxygen reduction, [15] CO 2 reduction, [22] and CO oxygenation. [23,24] For the case of Oxygen Reduction Reaction, experiments and theoretical calculations demonstrated that the strength of the interaction with OH decreases for increasingly generalisedcoordinated sites. In turn the outcome of a coordination-activity analysis displays a characteristic volcano-shape with sites with GCN = 8.33 at its top.…”
Section: Characterisation Of Pt-nps Architectures and Active Sitesmentioning
confidence: 99%